PKC (Protein Kinase C)-δ Modulates AT (Antithrombin) Signaling in Vascular Endothelial Cells. Issue 7 (July 2020) - Panicker, Sumith R.; Biswas, Indranil; Giri, Hemant; Cai, Xiaofeng; Rezaie, Alireza R.
Abstract : Objective: Native and latent conformers of AT (antithrombin) induce anti-inflammatory and proapoptotic signaling activities, respectively, in vascular endothelial cells by unknown mechanisms. Synd-4 (syndecan-4) has been identified as a receptor that is involved in transmitting signaling activities of AT in endothelial cells. Approach and Results: In this study, we used flow cytometry, signaling assays, immunoblotting and confocal immunofluorescence microscopy to investigate the mechanism of the paradoxical signaling activities of high-affinity heparin (native) and low-affinity heparin (latent) conformers of AT in endothelial cells. We discovered that native AT binds to glycosaminoglycans on vascular endothelial cells via its heparin-binding D-helix to induce anti-inflammatory signaling responses by recruiting PKC (protein kinase C)-δ to the plasma membrane and promoting phosphorylation of the Synd-4 cytoplasmic domain at Ser179. By contrast, the binding of latent AT to endothelial cells to a site(s), which is not competed by the native AT, induces a proapoptotic effect by localizing PKC-δ to the perinuclear/nuclear compartment in endothelial cells. Overexpression of a dominant-negative form of PKC-δ resulted in inhibition of anti-inflammatory and proapoptotic signaling activities of both native and latent AT. Conclusions: These results indicate that the native and latent conformers of AT may exert their distinct intracellular signaling effects through differentially modulating the subcellular localization of PKC-δ in endothelial cells. Abstract : Supplemental Digital Content is available in the text.